A hands-on introduction to forensic science : cracking the case - Okuda, Mark M.; Stephenson, Frank H. (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
"One failing of many forensic science textbooks is the isolation of chapters into compartmentalized units. This format prevents students from understanding the connection between material learned in previous chapters with that of the current chapter. Using a unique format, A Hands-On Introduction to Forensic Science: Cracking the Case approaches the topic of forensic science from a real-life perspective in a way that these vital connections are encouraged and established.The book utilizes an ongoing fictional narrative throughout, entertaining students as it provides hands-on learning in order to "crack the case." As two investigators try to solve a missing persons case, each succeeding chapter reveals new characters, new information, and new physical evidence to be processed. A full range of topics are covered, including processing the crime scene, lifting prints, trace and blood evidence, DNA and mtDNA sequencing, ballistics, skeletal remains, and court testimony. Following the storyline, students are introduced to the appropriate science necessary to process the physical evidence, including math, physics, chemistry, and biology. The final element of each chapter includes a series of cost-effective, field-tested lab activities that train students in processing, analyzing, and documenting the physical evidence revealed in the narrative. Practical and realistic in its approach, this book enables students to understand how forensic science operates in the real world" --
"Preface The aim of this book is to present a novel way of teaching forensic science and, more importantly, a different way of presenting any science discipline whether it be chemistry, physics, or biology. Most science textbooks today are formatted and presented in a compartmentalized manner; students are likely to encounter a chapter entitled "Cell Structure and Function" in a biology textbook, or "States of Matter" in a chemistry textbook, or "Newton's First Law of Motion-Inertia" in a physics textbook, or "Blood Spatter" in a forensic textbook. These compartmentalized units present an extensive list of vocabulary words as well as scientific principles and concepts to be mastered. The student take notes, conducts lab experiments and, at the conclusion of the unit, is evaluated by some form of assessment. This cycle repeats itself with the next chapter until the course is completed at the end of the academic year. This format often lacks the connections learned in prior chapters to the current chapter under study. Science on the other hand is about making connections. The disconnect that commonly exists between science textbooks, science courses and the way real science operates will be addressed in this manuscript. Science works with a problem or an observation which requires an integrated approach involving many different disciplines of science coming together and the connections that these disciplines can provide to help solve a problem or explain an observation. This book attempts to capture the student's interest by means of a unique format. It begins with a story about two characters who go about solving a missing persons case"--
Includes bibliographical references and index.
Keywords: Criminal investigation; Forensic ballistics; Chemistry, Forensic; LAW / Criminal Law / General; LAW / Forensic Science